A dental composite resin and its preparation method and application
By adding surface hydrophobic modified bioactive glass to dental composite resin, the secondary caries caused by micro gaps in dental composite resin is solved, and the rapid surface mineralization and interface closure of dental composite resin is achieved, which significantly improves its effect in preventing secondary caries.
Patent Information
- Application Number
- CN202410491294.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-23
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-04-23
AI Technical Summary
Dental composite resin shrinks during the curing process and damages the tissues of the restoration edges and holes during use, resulting in tiny gaps at the bonding interface between the restoration and the surrounding teeth, causing micro leakage, enrichment of caries, and thus leading to the formation of secondary caries.
Adding surface hydrophobic modified bioactive glass to dental composite resins improves the bonding strength of inorganic components with the resin matrix, and retains its mineralization ability, and uses mineralization to close microslits to prevent secondary caries.
By improving interface compatibility and mechanical properties, dental composite resins show rapid surface mineralization ability in the physiological environment, forming a dense hydroxyapatite layer, effectively closing microslits and avoiding the formation of secondary caries, which has important clinical value.
Smart Images

Figure CN118078644B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of biomedical materials, and in particular to a dental composite resin and a preparation method and application thereof. Background Art
[0002] Caries is a disease in which the hard tissues of teeth are destroyed chronically. Caries and its complications can aggravate or induce systemic diseases and seriously endanger human health. It has been listed as the third largest non-communicable disease by the World Health Organization. The results of the Global Economic Burden of Disease Study released by Lancet in 2016 showed that caries in permanent teeth ranked first, bringing a heavy economic burden to the healthcare system. Filling and restoration is currently the main means of treating caries. Dental composite resin has become the most widely used filling and restoration material due to its excellent aesthetic and mechanical properties and easy operation. However, due to the volume shrinkage of composite resin during curing, or damage to the tooth tissue at the edge of the restoration and the cavity during subsequent use, tiny gaps are easily formed at the bonding interface between the restoration and the surrounding tooth, resulting in microleakage. This microleakage allows cariogenic bacteria (such as Streptococcus mutans) to accumulate here, which in turn triggers acidic medium-induced interface deterioration and demineralization of tooth tissue around the restoration, ultimately leading to the formation of secondary caries. These problems shorten the service life of the restoration and may eventually lead to failure of tooth restoration. Studies have shown that secondary caries has become the main cause of failure of dental composite resin restorations in clinical practice. Therefore, the development of dental composite resins with the function of preventing secondary caries has important clinical application value.
[0003] There are currently two main strategies for preventing secondary caries: inhibiting the adhesion of acid-producing bacteria or promoting the remineralization of demineralized dentin. However, acid-producing bacteria in the oral cavity are basically conditional pathogens, and commonly used broad-spectrum antibacterial agents lack specificity and have limited duration of action. In addition, the large-scale use of broad-spectrum antibacterial drugs may also cause microecological imbalance of normal oral flora, so the clinical effect is not ideal. Promoting the remineralization of demineralized dentin means inducing the remineralization of surrounding demineralized dentin in the oral environment with the help of the mineralizing components in the resin, thereby avoiding excessive bacterial invasion. However, since the interface gap still exists, this measure can only slow down the development of secondary caries, and cannot eliminate the formation of secondary caries from the root. If minerals are formed at the interface gap with the help of a mineralizing agent to block the gap, the formation of secondary caries may be fundamentally avoided. Bioactive glass (BG) can react with saliva to quickly induce mineralization to form hydroxyapatite (HA), and is expected to become an excellent mineralizer. Summary of the invention
[0004] The purpose of the present invention is to provide a dental composite resin and a preparation method and application thereof; the present invention improves the bonding strength between an inorganic component and a resin matrix and retains its mineralization ability in the resin matrix by adding bioactive glass having a contact angle with water of 35° to 43° into the dental composite resin, thereby overcoming the contradiction between the mineralization ability of traditional inorganic components in the dental composite resin and the interface compatibility, and utilizes mineralization to seal micro-gaps to achieve the purpose of preventing secondary caries.
[0005] The present invention first provides a dental composite resin, which is made of components including the following raw materials: an inorganic filler, a resin matrix and a photoinitiator system;
[0006] The inorganic filler is a surface hydrophobically modified bioactive glass or a surface hydrophobically modified bioactive glass and other inorganic fillers without mineralization ability;
[0007] The contact angle between the surface hydrophobically modified bioactive glass and water is 35° to 43°;
[0008] The resin matrix is composed of a rigid monomer and a diluent monomer;
[0009] The photoinitiator system consists of a photoinitiator and a co-initiator.
[0010] In the dental composite resin, the inorganic filler has a mass percentage of 30% to 70% based on the total mass of the dental composite resin; specifically, it may be 30%, 50% or 70%;
[0011] Based on the total mass of the resin matrix and the photoinitiator system, the mass percentage of the photoinitiator system is 1% to 2%, and can be specifically 1%.
[0012] In the dental composite resin, the inorganic filler having no mineralization ability is at least one of silicon dioxide, hydroxyapatite, titanium dioxide and zirconium oxide;
[0013] The bioactive glass is a phosphosilicate bioactive glass;
[0014] The rigid monomer is at least one of bisphenol A diglycidyl methacrylate (bis-GMA), glycerophosphodimethacrylate (GPDM) and urethane dimethacrylate (UDMA);
[0015] The diluent monomer is at least one of triethylene glycol dimethacrylate (TEGDMA), methyl methacrylate (MMA), 4-hydroxybutyl acrylate, 1,6-hexanediol diacrylate, bisethoxybisphenol-A dimethacrylate and hydroxyethyl methacrylate;
[0016] The photoinitiator is at least one of camphorquinone (CQ), dimethyl benzoate (DMPA), benzophenone, hydroxycyclohexyl acetophenone and dihexyloxy acetophenone;
[0017] The auxiliary initiator is at least one of dimethylaminoethyl methacrylate (DMAEMA), methyl benzoylformate, ethyl p-dimethylaminobenzoate and trimethylbenzoylphenylethyl phosphate.
[0018] In the above dental composite resin, the bioactive glass is at least one of 45S5 bioactive glass, 58S bioactive glass, pH neutral bioactive glass (PSC) and A / W glass-ceramics.
[0019] In the above dental composite resin, the mass ratio of the rigid monomer to the diluent monomer is 1 to 3:1; specifically, it can be 1:1;
[0020] The mass ratio of the photoinitiator to the co-initiator is 1:1-4; specifically, it can be 1:4;
[0021] When the inorganic filler is composed of surface hydrophobically modified bioactive glass and other inorganic fillers without mineralization ability, the surface hydrophobically modified bioactive glass accounts for 30% to 100% of the total mass of the inorganic filler, but not 100%; specifically, it can be 30% to 99%.
[0022] The particle size of the inorganic filler without mineralization ability is all commonly used particle sizes known in the art, such as below 400 mesh (diameter less than 30 μm); 400-200 mesh (diameter 30-70 μm); 200-120 mesh (diameter 70-120 μm); 120-80 mesh (diameter 120-200 μm).
[0023] The particle size of the bioactive glass is any commonly used particle size known in the art, such as below 400 mesh (diameter less than 30 μm); 400-200 mesh (diameter 30-70 μm); 200-120 mesh (diameter 70-120 μm); 120-80 mesh (diameter 120-200 μm); specifically, the particle size of the bioactive glass is less than 38 μm.
[0024] In the above-mentioned dental composite resin, the preparation method of the surface hydrophobically modified bioactive glass comprises the following steps: adding the bioactive glass to a mixed solution consisting of anhydrous ethanol, water, and 3-isobutylacryloxypropyltrimethoxysilane, and stirring at room temperature for 48h to 60h to obtain the surface hydrophobically modified bioactive glass.
[0025] Specifically, stirring is performed at room temperature for 48 hours; the room temperature is well known to those skilled in the art, and is generally 15-35°C.
[0026] The present invention also provides a method for preparing the dental composite resin, comprising the following steps: mixing the inorganic filler, the resin matrix and the photoinitiator system.
[0027] The above-mentioned preparation method further comprises the step of light curing after mixing.
[0028] Specifically, the light curing is performed by irradiating the film with visible light having a wavelength of 460-480 nm for 20 seconds.
[0029] Finally, the present invention provides the use of the dental composite resin in preparing a filling for preventing and / or treating secondary caries.
[0030] The present invention has the following beneficial effects:
[0031] (1) The inorganic filler in the present invention includes a bioactive glass with a hydrophobic surface modification. Compared with the conventional mineralization-promoting inorganic filler, the filler greatly improves the interfacial compatibility, improves its mechanical properties while retaining a fairly strong bioactivity, thus overcoming the contradiction between bioactivity and interfacial compatibility in dental composite resins;
[0032] (2) After the dental composite resin is prepared by light curing, due to the introduction of bioactive glass, the composite resin can exhibit rapid surface mineralization ability in physiological environments (such as saliva and body fluids), and a dense hydroxyapatite layer with a thickness of tens of microns can be formed within a few days;
[0033] (3) Secondary caries is caused by cariogenic bacteria entering the micro-gaps created after the dental composite resin is cured, leading to dentin demineralization and entry into the dentinal tubules. The rapid surface mineralization ability means that the dental composite resin can exhibit the characteristics of self-growth in the oral environment, thereby eliminating micro-gaps and avoiding the formation of secondary caries, which has important clinical value. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 The mechanical properties of the dental composite resins prepared in Examples 1-4.
[0035] Figure 2 The mineralization properties of the dental composite resins prepared in Examples 1-4; wherein, Figure 2 a in the figure is the XRD result before immersion in artificial saliva, and b is the XRD result after immersion in artificial saliva for one week.
[0036] Figure 3 The surface morphology of the dental composite resin prepared in the example before and after being immersed in artificial saliva for one week.
[0037] Figure 4The cross-sectional SEM images of the dental composite resins prepared in Examples 1 to 4 after being immersed in artificial saliva for one week; wherein the red dotted lines represent the generated hydroxyapatite layers; Figure 4 a is Example 4; b is Example 3; c is Example 2; d is Example 1. DETAILED DESCRIPTION
[0038] The present invention is further described in detail below in conjunction with specific embodiments. The given examples are only for illustrating the present invention, but not for limiting the scope of the present invention.
[0039] The experimental methods in the following examples are all conventional methods unless otherwise specified.
[0040] The quantitative tests in the following examples were all repeated three times, and the results were averaged.
[0041] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.
[0042] The PSC bioactive glass used in the following examples was purchased from China Huakui Technology Taizhou Co., Ltd.
[0043] Example 1
[0044] (1) Disperse 1 g of PSC bioactive glass with a particle size of less than 38 μm into 9 g of anhydrous ethanol and 1 g of water, and add 1 g of TPM (3-isobutylacryloxypropyltrimethoxysilane, CAS: 2530-85-0). Stir the mixture evenly by magnetic stirring at room temperature (25°C). After 48 h, centrifuge the mixture, wash with anhydrous ethanol, and dry it. The resulting product is a surface hydrophobically modified PSC bioactive glass.
[0045] The water contact angle of the sample after the product was pressed under a pressure of 5 MPa for 15 seconds was measured using a contact angle meter. The water contact angle of the pressed sample was about 37°.
[0046] (2) 4.95 g of bis-GMA (bisphenol A diglycidyl methacrylate, CAS: 1565-94-2), 4.95 g of TEGDMA (triethylene glycol dimethacrylate, CAS: 109-16-0), 0.08 g of DMAEMA (dimethylaminoethyl methacrylate, CAS: 2867-47-2) and 0.02 g of CQ (camphorquinone, CAS: 10373-78-1) were mixed and stirred at 60 °C for 1 hour in a dark environment to obtain a clear and transparent mixed solution of the resin matrix and the photoinitiator system.
[0047] (3) 0.7 g of surface hydrophobically modified PSC bioactive glass was added to the mixed solution of 0.3 g of resin matrix and photoinitiator system, and the mixture was placed in a degassing mixer for 2 min. The mixed sample was then transferred into a mold and cured by irradiation with visible light at a wavelength of 460-480 nm for 20 s. After demolding, a dental composite resin was obtained.
[0048] According to the international standard "ISO 4049-2009", the mechanical properties of dental composite resins were tested using a universal testing machine (MTS E42). The composite resin was immersed in artificial saliva (50 mmol / L KCl, 1.5 mmol / L CaCl2, 0.9mmol / L KH2PO4 and 20 mmol / L Tris, the solvent was double distilled water), and after one week, the surface mineralization properties were tested and observed using an X-ray diffractometer (XRD) and a scanning electron microscope (SEM). The XRD scanning range was 5° to 70°, and the scanning rate was 4° / min. Before the SEM test, the sample was adhered to the SEM sample stage with conductive glue, and gold was sprayed (current was 20 mA, time was 120s), and then the sample cross section and surface morphology were observed using SEM (power-on voltage was 5 kV).
[0049] The flexural strength of the dental composite resin is 72.9±1.3MPa (see Figure 1 ), which is in line with international standards. The XRD results are significantly different from those before immersion in artificial saliva (see Figure 2 ). SEM can clearly show that a dense needle-shaped hydroxyapatite layer is formed on the surface of the composite resin after being immersed in artificial saliva (see Figure 3 ), from the cross section, we can see that the thickness of the hydroxyapatite layer can reach 25~30μm, which can effectively close the micro-gaps caused by polymerization shrinkage (see Figure 4 ).
[0050] Example 2
[0051] The preparation method is the same as that in Example 1, except that in step (3), 0.5 g of the surface hydrophobically modified PSC bioactive glass is added to the mixed solution of 0.5 g of the resin matrix and the photoinitiator system.
[0052] The flexural strength of the dental composite resin prepared in this embodiment is 87.6±2.1MPa, which meets international standards. The XRD results are significantly different from those before immersion in artificial saliva. Through SEM, it can be clearly seen that a dense needle-shaped hydroxyapatite layer is produced on the surface of the composite resin after immersion in artificial saliva. From the cross section, it can be seen that the thickness of the hydroxyapatite layer can reach 10~15μm, which can effectively close the micro-gaps generated by polymerization shrinkage.
[0053] Example 3
[0054] The preparation method is the same as that in Example 1, except that in step (3), 0.3 g of surface hydrophobically modified PSC bioactive glass is added to the mixed solution of 0.7 g of resin matrix and photoinitiator system.
[0055] The flexural strength of the dental composite resin prepared in this embodiment is 91.3±1.6MPa, which meets international standards. The XRD results are significantly different from those before immersion in artificial saliva. Through SEM, it can be clearly seen that a dense needle-shaped hydroxyapatite layer is produced on the surface of the composite resin after immersion in artificial saliva. From the cross section, it can be seen that the thickness of the hydroxyapatite layer can be about 5μm, which has a certain effect on closing the micro-gaps generated by polymerization shrinkage.
[0056] Example 4
[0057] The preparation method is the same as that in Example 1, except that in step (3), 0.1 g of the surface hydrophobically modified PSC bioactive glass is added to the mixed solution of 0.9 g of the resin matrix and the photoinitiator system.
[0058] The flexural strength of the dental composite resin prepared in this embodiment is 81.0±1.9MPa, which meets international standards. The XRD results are not significantly different from those before immersion in artificial saliva. No obvious hydroxyapatite is observed on the surface by SEM, which is consistent with the XRD results, and the micro-cracks generated by polymerization shrinkage cannot be closed.
[0059] Comparative Example 1
[0060] The preparation method is the same as that in Example 1, except that the bioactive glass uses PSC bioactive glass whose surface is not hydrophobically modified; in step (3), the amount of PSC bioactive glass added without hydrophobic modification is 10%, 30%, 50% or 70% of the total mass of the dental composite resin. The mechanical properties of the obtained dental composite resin are shown in Figure 1 ,Depend on Figure 1 It can be seen that the mechanical properties of the composite resin prepared from the bioactive glass without hydrophobic modification at the same mass ratio are significantly weaker than those of the composite resin prepared from the bioactive glass with surface hydrophobic modification.
Claims
1. A dental composite resin, characterized in that: The dental composite resin is made of the following raw material components: inorganic filler, resin matrix and photoinitiator system; The inorganic filler is a bioactive glass with a hydrophobic surface modification; the bioactive glass is a PSC bioactive glass; The contact angle between the surface hydrophobically modified bioactive glass and water is 35° to 43°; The resin matrix is composed of a rigid monomer and a diluent monomer; The photoinitiator system is composed of a photoinitiator and a co-initiator; The mass percentage of the inorganic filler is 50% to 70% based on the total mass of the dental composite resin; The rigid monomer is at least one of bisphenol A glycidyl dimethacrylate, glycerophosphoric acid dimethacrylate and carbamate dimethacrylate; The diluent monomer is at least one of triethylene glycol dimethacrylate, methyl methacrylate, 4-hydroxybutyl acrylate, 1,6-hexanediol diacrylate, bisethoxybisphenol-A dimethacrylate and hydroxyethyl methacrylate; The photoinitiator is at least one of camphorquinone, benzoin dimethyl ether, benzophenone, hydroxycyclohexyl acetophenone and dihexyloxy acetophenone; The auxiliary initiator is at least one of dimethylaminoethyl methacrylate, methyl benzoylformate, ethyl p-dimethylaminobenzoate and trimethylbenzoylphenyl ethyl phosphate; The preparation method of the surface hydrophobically modified bioactive glass comprises the following steps: adding the bioactive glass into a mixed solution consisting of anhydrous ethanol, water and 3-isobutylacryloxypropyltrimethoxysilane, stirring at room temperature for 48 hours to 60 hours, and obtaining the surface hydrophobically modified bioactive glass.
2. The dental composite resin according to claim 1, characterized in that: Based on the total mass of the resin matrix and the photoinitiator system, the mass percentage of the photoinitiator system is 1% to 2%.
3. The dental composite resin according to claim 1, characterized in that: The mass ratio of the rigid monomer to the diluent monomer is 1 to 3:1; The mass ratio of the photoinitiator to the co-initiator is 1:1-4.
4. The method for preparing a dental composite resin according to any one of claims 1 to 3, characterized in that: The method comprises the following steps: mixing the inorganic filler, the resin matrix and the photoinitiator system.
5. The preparation method according to claim 4, characterized in that: The preparation method further comprises a light curing step after mixing.
6. Use of the dental composite resin according to any one of claims 1 to 3 in preparing a filling for preventing and / or treating secondary caries.
Citation Information
Patent Citations
Modified bioactive glass / polyacrylamide / oxidized sodium alginate hydrogel dressing and preparation method thereof
CN106729927A
Composite resin with low contraction stress containing dimethacrylate with long oxyalkyl chain for dental department and preparation method of composite resin
CN108578249A
Self-adhesive resin cement composition for dental department
CN112515974A
Strongly mineralized bioactive glass with good interfacial compatibility with acrylic resin and preparation method and application of strongly mineralized bioactive glass
CN117965041A